Y a-t-il une forme de vie humaine chez Spinoza ? - Ursula Renz (Astérion)
In recent years, there has been an increasing interest in the concept of the human life-form in philosophy. On the one hand, some have argued that in order to conceive of an individual living being in terms of specific properties, it is necessary to refer to the life form shared by the members of its species. On the other hand, it has been argued that the idea of a good life for humans requires that we think of man’s possible actions and passions in the horizon of the human life form. This article examines whether there is in Spinoza an idea of a specific life-form of humans. Taking the notion of a specifically human good, which is invoked in the Metaphysical Thoughts and in a few parallel passages in the Ethics, it first argues that Spinoza does in fact assume the idea of human species in his philosophy. Examining the correspondence with Henry Oldenburg, it next argues that an interpretation of Spinoza’s views on modality can be developed in a way that allows for the notion of (non-actualized) human capacities. It then discusses how the idea of species is related with the conatus doctrine, before it concludes with a few remarks on the contribution of culture to the development of the human life form. Altogether, the article defends the twofold view that there is conceptual space for the notion of a human life-form in Spinoza and that this notion is crucial for several aspects of Spinoza’s philosophy.